2020
DOI: 10.2196/17071
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Associations of Daily Changes in Sleep and Depression Core Symptoms in Patients Suffering From Major Depressive Disorder: Idiographic Time-Series Analysis

Abstract: Background There is a strong link between sleep and major depression; however, the causal relationship remains unclear. In particular, it is unknown whether changes in depression core symptoms precede or follow changes in sleep, and whether a longer or shorter sleep duration is related to improvements of depression core symptoms. Objective The aim of this study was to investigate temporal associations between sleep and depression in patients suffering f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This is, in part, a secondary analysis of data previously analyzed in the work of Lorenz et al (2020) on the idiographic association between sleep and depression. Our analyses were preregistered after data collection and before secondary data analysis using the template for preregistration of experience sampling studies by Kirtley et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…This is, in part, a secondary analysis of data previously analyzed in the work of Lorenz et al (2020) on the idiographic association between sleep and depression. Our analyses were preregistered after data collection and before secondary data analysis using the template for preregistration of experience sampling studies by Kirtley et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…However, the causal relationship remains unclear. It is, for instance, unknown whether changes in depression symptoms precede or follow changes in sleep, and whether a longer or shorter sleep duration is related to improvements of depression core symptoms (Borbely et al, 2016; Lorenz et al, 2020). Investigating this may further explain how and when an acute SD exerts its rapid antidepressant effect and why it typically relapses after subsequent sleep occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, objective and subjective sleep variables were associated with symptoms of anxiety, depression, and fatigue, highlighting the importance of considering the relationship between mental health/fatigue symptoms and sleep. Previous research in the general population and among individuals with depression has demonstrated that worse depression is associated with poorer objective and subjective sleep measures (Jackowska et al, 2016; Lorenz, Sander, Ivanova, & Hegerl, 2020). Within the IBD population, both the PSQI and the PROMIS Sleep Disturbance measures have been significantly associated with depression (Ananthakrishnan et al, 2013; Sochal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%